PORTRAYALS OF LESBIANS IN ALBERTHEME ENDAH'S NOVEL ENTITLED DICINTAI JO - Annisa Masfuana, - (2006)
The research paper is entitled "The Portrayal of Lesbian in Alberthiene Endah's Dicintai Jo". In this study, the writer focuses on the portrayal of four lesbians characters in the story and used queer theory as the framework of the study. The aims of this study were to find types of women who portrayed as lesbians in the story and to know kinds of actions that indicated the women characters as lesbians. From the study, the writer found that there are some similarities of lesbian characterization performed by the author. The data found concerning the portrayal of lesbian is then framed and analyzed based on queer theory. After conducting the study, the writer found that lesbianism is socially constructed, not biologically happened, means that a woman became a lesbian because various social factors forces her in being lesbian. Pembimbing I Dr. Bachrudin Musthafa, M.A. Pembimbing II Della N. Kartika Sari, S.Pd.